(untitled) (TSUL LEGAL REPORT, 2026)
In this article, it is thoroughly analyzed how the use of the Internet has acquired the status of a fundamental right within the framework of international law and how this process has been successful in some cases. The study examines such important legal frameworks as regional normative documents on human rights, and statements of the Special Rapporteurs, decisions of the UN Human Rights Council as well as the experience of new states. This study reveals important contradictions through theoretical analysis and practical study of Internet disruptions and access barriers. On the one hand, at least at the theoretical level, there is growing international consensus on the issue of digital rights. However, real practice demonstrates an even more alarming picture: government structures continue to impose restrictions largely unpunished, often relying on vague interpretations of national security, which indicates that international law does not have sufficient force to act as an effective barrier. The study shows that although access to the Internet has not achieved the status of an autonomous human right in compulsory contract law, its functional necessity for the exercise of established rights (freedom of expression, freedom of assembly, and freedom of information) has created what can be called de facto directly through the back door.